Fatty acid metabolism after short-term fasting: POMC response and EPA signal maintain homeostasis in tilapia - Yu, Xiaozheng; Zhu, Tiansheng; Yu, Yang; Cai, Ran; Li, Meiqing; Sun, Caiyun; Li, Wensheng (Frontiers in Endocrinology, 2025)
Detecting and responding to fluctuations in fatty acid levels is crucial for maintaining the homeostasis of fatty acid metabolism. This study examined changes in neuropeptide levels and fatty acid sensing systems in tilapia following 24-hour fasting. Subsequently, an EPA compensation experiment was conducted to examine the regulatory effects of hypothalamic neuropeptides on feeding activity, fatty acid sensing systems activation, and alterations in AMPK and AKT signaling pathways in tilapia. After fasting, the neuropeptide Y signals in the preglomerular nucleus region increased significantly, while the POMC in the lateral tuberal nucleus significantly decreased. There was a significant increase in most long-chain fatty acids, excluding the EPA which declined. Fasting activates fatty acid sensing systems regulated by fatty acid metabolism and mitochondrial activity in the hypothalamus, and those regulated by CD36, mitochondrial activity and PKC in the liver. However, it inhibited systems regulated by fatty acid metabolism and lipoprotein lipase in the liver. Intraperitoneal EPA injection raised pomc mRNA levels in the hypothalamus after short-term fasting and curtailed food intake. EPA compensation inhibited the liver fatty acid metabolism, CD36, and mitochondrial activity-related fatty acid sensing systems, and lipoprotein lipase-regulated fatty acid sensing systems in the hypothalamus while activating lipoprotein lipase-regulated fatty acid sensing systems in the liver. Moreover, EPA suppressed the AMPK pathway in both tissues. Following fasting, serum EPA levels decreased, accompanied by lower POMC in the brain and activation of the fatty acid sensing systems in hypothalamus and liver. EPA compensation inhibited the AMPK pathway, increased pomc mRNA in the hypothalamus and suppressed food intake as a satiation factor. This research offers insights into how the central nervous system and peripheral tissues respond to fatty acid levels during hunger in tilapia.